Paper-Based versus Mobile Apps for Colorectal Cancer Screening in COVID-19 Pandemic Setting - Handaya, Adeodatus Yuda; Hardianti, Mardiah Suci; Rinonce, Hanggoro Tri; Werdana, Victor Agastya Pramudya; Fauzi, Aditya Rifqi; Andrew, Joshua; Hanif, Ahmad Shafa; Tjendra, Kevin Radinal; Aditya, Azriel Farrel Kresna (Universitas Airlangga, 2023)
Background: The incidence of colorectal cancer (CRC) in Asia has kept increasing in the last decade. The morbidity and mortality for CRC can be reduced with early detection; however, mass CRC screening with imaging modalities such as colonoscopy, CT scan, or MRI is unfeasible in developing countries such as Indonesia. Asia Pacific Colorectal Screening (APCS) is utilized to stratify individual CRC risk. Online screening via mobile application is an alternative method to ensure the continuity of community screening without risking COVID-19 transmission. Objective: We conducted a descriptive study to evaluate CRC risk using APCS in two different villages. Methods: This is a cross-sectional study involving 925 and 207 subjects in 2019 and 2020, respectively. The APCS survey in 2019 was done before the COVID-19 pandemic with paper-based questionnaires and direct assessment by door-to-door approach. Meanwhile, the APCS survey in 2020 was done during the COVID-19 pandemic using websites and mobile apps available for Android and iOS. We gathered participants' characteristics and the APCS score in both groups and tabulated them. Results: In 2019, out of 925 subjects; 472 (51%) have been classified an average risk of CRC, 370 (40%) have been classified as having a moderate risk of CRC, and 83 (9%) have been classified as in high risk of CRC. In 2020, out of 207 subjects; 106 (51.2%) have been classified as the average risk of CRC, 86 (41.5%) have been classified as the moderate risk of CRC, and 15 (7.3%) have been classified as high risk of CRC. Conclusion: Although there was a decrease in the participation of the screening program with mobile applications in the pandemic era compared with paper-based questionnaires before the pandemic era, online screening using APCS in mobile applications is a preferred alternative for an effective screening method in this pandemic and possibly in the future in Indonesia.